Root fracture as complication of surgically assisted rapid maxillary expansion - de Azambuja Carvalho, Pedro Henrique [UNESP]; Garcia, Robson Rodrigues; Estrela, Cristiane Bonanato; Filho, Valfrido Antônio Pereira [UNESP] (Wolters Kluwer, 2018)
A 23 year old male patient was submitted to surgical assisted rapid maxillary expansion (SARME). There were any postoperative complications until the finish of orthodontic expansion process. However, in the 30th postoperative day, patient mentioned pain in upper central incisor. Periapical radiography evidenced a root fracture of central upper right incisor. After endodontic treatment, the fractured apex was removed. After 3 years of follow-up, the patient finished orthodontics, and the damaged tooth was in good aspect. Apical fracture is an unexpected complication of SARME. However, follow-up and correct treatment lead to a good prognosis for tooth maintenance.
Keywords: Case report; Complication; Maxillary expansion; Root fracture